Ethnicity Deconstructed: The breakup of the former Yugoslavia and personal reflections on nationalism, identity and displacement - Petrovic, Edit (Culture, 1995)
This article is a self-reflexive attempt to bring to light the different problems presented by the idiom of "ethnicity." The main obstacle to attempting the self-reflexive approach is a paradox: it is difficult to derive scientific credibility from elaborations based on implicit feelings, inconsistencies, and unrelated experiences, yet these same elements are seen as relevant ethnographic materials. I describe personal experiences that revolve around three themes: nationalism, identity and displacement. Implicitly, I argue that: a) "ethnicity" is entirely a matter of context that translates into unrelated experiences and contradictory feelings that shape and transform our sense of who we are, or who we are not; b) situations where individuals are forced to expose their ethnic identity and declare "ethnic loyalties" may influence some to become aware that they have no ethnic identity (forced attachment equals detachment); c) there are no groups that are "more nationalistic" or "less nationalistic" - erupting nationalism in former Yugoslavia is seen mainly as a resuit of skillful political manipulation, rather than just a "thing out there"; and d) displacement provides a needed contrastive perspective for articulating one’s own identity.